Effect of Moderate-to-Severe Iodine Deficiency in Early Pregnancy on Subclinical Hypothyroidism: A Longitudinal Study in an Iodine-Sufficient Region in China - Wang, Taotao; Liu, Yanqiu; Kong, Qianqian; Cao, Xiaoxia; Liu, Yuzhou; Xia, Song; Zheng, Tingting; Yu, Li (Frontiers in Nutrition, 2022)
Objective: To investigate iodine status among pregnant women in an iodine-sufficient region in China after the implementation of revised universal salt iodization (USI) standards in 2012 and assess the association between urinary iodine concentrations (UIC) in early pregnancy and the incidence of subclinical hypothyroidism (SCH) in euthyroid women negative for antithyroid Ab during different trimesters. Methods: We measured the iodine status of 1264 pregnant women, and performed follow-up assessment of thyroid function at 20 and 30 weeks of gestation among a cohort of 250 euthyroid women. We assessed the association of UIC in the 1st trimester with the incidence of SCH in subsequent trimesters. UIC and serum free triiodothyronine (FT3), free thyroxine (FT4), thyroid-stimulating hormone (TSH), thyroid peroxidase antibody (TPOAb), and thyroglobulin antibody (TgAb) were measured. Results: The median UIC was 135.95 μg/L among 1264 women. Serum FT4 level was significantly higher in the group of UIC 150 to 249 μg/L compared with other UIC groups (P < 0.001). TSH was significantly higher in the UIC more than or equal to 250 μg/L group than the UIC 150 to 249 g/L group (P = 0.043). Of the 250 euthyroid women negative for antithyroid Ab (TSH value of 2.5–3.55 mU/L) in the 1st trimester, pregnant women with UIC lower than 100 μg/L in the 1st trimester exhibited a significantly increased risk of SCH (odds ratio [OR] = 2.47; 95% confidence interval [CI] = 1.22–5.71; P = 0.012, according to the Chinese Medical Association criteria; OR = 5.22, 95% CI = 1.73–6.09, P = 0.004, according to ATA criteria) during the latter half of pregnancy compared with the UIC 150 to 249 μg/L group. Conclusion: Moderate-to-severe iodine deficiency (UIC lower than 100 μg/L) in the 1st trimester was associated with a significantly higher risk of SCH during the 2nd or 3rd trimesters among euthyroid pregnant women who had negative for antithyroid Ab. Women with SCH during pregnancy require regular UIC tests to maintain appropriate iodine status.